Agama Sebagai Dasar Kepemimpinan (Suatu Tinjauan dari Segi Persuasive Leadership) - Hamzah, Mohd. Asrie (Jurnal Aplikasi Manajemen, 2015)
Leadership problem is a sosial phenomenon (sympthom) which ishappened inevery nation, place, andera, with different condition and situation. These make a complexterm in defining the same conception about the main problem. Further development showedthat leader is not functionable in isolation, but face to face with many people that must be ledby herself/himself in social context, cultural or even the specific environment which is generallynamed situation. Leadership is a skill to affect human/ its subordinate to do a jobaccording to the leaders'want. Religion which is based on psychology law, tradition, believeor class is universally and apply to each human. From these elements can be taken thebenefit as much as possible to arrange that leadership. Due to tradition, believe and class,each can synchronize the soul among people. Religionfillsthe humansoul, therefore the motionand vibrate the soul (conscience) is led byreligion. Ifthe soul can set the action andreaction with the act, then of course that contains thesoul of religion and speech canberegulated according to religious charitiescon cerned. Thus, it affects in the way faithbasedleadership, is to practice the teachings of religion, which is typically called a solicitationor exemplary leadership.